Microstructure and Properties of Supersonic Plasma Sprayed NiCrBSi-Diamond Composite Coatings - SUN Haoran, ZHANG Di, JIA Lei, PANG Chengyu, DONG Shushan, ZHOU Yongxin (Cailiao Baohu)
To improve the mechanical properties and wear and corrosion resistance of 921A steel surface under marine environment， two kinds of coatings were prepared on the surface of 921A steel by supersonic plasma spraying technology.The powders used were NiCrBSi spherical powder and NiCrBSi composite powder with chromium plated diamond (20～40 μm).The prepared coating samples were labeled as coating N and coating ND respectively， and the spray substrate was labeled as sample 921A in the subsequent comparison test.Moreover， the phase composition of the coating was analyzed，the cross section morphology and element composition of the coating were observed，the microhardness and tensile bond strength of the coating were tested， the friction coefficient and volume wear rate of the coating with Si3N4 ball under the reciprocating friction and wear mode were measured， and the open circuit potential and self-corrosion current density of the coating were fitted.Results showed that compared with the coating N prepared by pure NiCrBSi powder， the microhardness and bonding strength of diamond composite coating ND were 1 016 HV and 50.156 MPa， which were 15.3%and 15.3%higher than those of coating N.Under the condition of 30 N load，Si3N4 ball as the grinding object and reciprocating time of 60 min， the average ND wear depth of diamond composite coating was 17.738 μm，exhibiting a 75.8%decrease relative to the substrate.The volume wear rate was 1.40×10－5 mm3/(N∙m)， which was only 20.7%of the substrate， and the friction coefficient was 0.229.At room temperature and 3.5%NaCl solution，the ND self-corrosion potential Ecorr of the diamond composite coating was－864 mV， which was 61 mV higher than that of the 921A substrate， and the self-corrosion current density Jcorr was 1.332×10－5 A/cm2， which was 77.9%lower than that of the 921A substrate.